f(x) = 3x + 9
y = 3x + 9
so 3x = y - 9
x = y/3 - 3
Therefore, the inverse function is g(x) = x/3 - 3
the answer is -3x = 0
3x-2y+9+9y-x = 2x+7y+9
-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5
9
Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "equals".
3x multiplied by (12x plus 9) is:3x(12x + 9)= (3x * 12x) + (3x * 9)= 36x2 + 27x
The equivalent expression of 3x-9 plus 3x plus 5 is negative 4.
4x3+12x2+3x+9
9x+3
3x + 9
the answer is -3x = 0
5x + 4 - 3x + 5 + 2x - 9 = 4x
3x-2y+9+9y-x = 2x+7y+9
4x + 2 = 3x + 9 x + 2 = 9 x = 7
The value of X in the equation 3x 2-12x plus 9 is 1.25.
3(x plus 3) expanded --> 3x+9
-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5